UM news: Recap 2024 - Corporate Communications Centre, - (Corporate Communications Centre, 2024)
The year 2024 brought significant achievements and advancements at UM. From groundbreaking research initiatives to innovative academic programs, the university continued to excel across various disciplines. Key milestones included community engagement projects, global partnerships, and advancements in sustainability efforts, reflecting UM's commitment to excellence and progress.